Characterization of efflux transport proteins of the human choroid plexus papilloma cell line HIBCPP, a functional in vitro model of the blood-cerebrospinal fluid barrier - Bernd, Alexandra Marion; Ott, Melanie; Schroten, Horst; Schwerk, Christian; Fricker, Gert (Pharmaceutical research, 2015)
Purpose: To characterize the human choroid plexus (CP) papilloma cell line HIBCPP with respect to ABC export protein expression and function in order to evaluate its use as an in vitro model to study carrier-mediated transport processes at the CP. Methods: Expression profiles of ABC transporters were studied by quantitative real-time PCR and Western Blot analysis. Functionality of transporters was investigated by means of uptake experiments and permeation studies carried out on permeable filter systems. In addition, immunohistochemistry served to study localization of ABCC1 and ABCC4. Results: Both qPCR and Western Blot revealed that ABC transporters known to be expressed in CP are also expressed in HIBCPP cells. Immunohistochemistry confirmed basolateral expression of ABCC1. Functionality of ABCC1, ABCC4, ABCB1 and ABCG2 could be shown in uptake assays. Conclusions: Altogether, the HIBCPP cells promise to be a functional and relevant in vitro tool to investigate transport processes at the blood-cerebrospinal fluid barrier.
Gesehen am 26.02.2018